Sistema web de gestión de publicaciones y documentación técnico-científico del área agroproductiva de la zona 4 - Zambrano Loor, Yasmina Lizetty (2019)
The purpose of this degree work was to develop a web-based system of technical-scientific documentation of the agro-productive area of Zone 4, to facilitate access to this information. For the execution of this work, it was carried out in compliance with the specific objectives and the use of the agile methodology Extreme Programming. In objective one, technical visits were made to the research department where the necessary requirements for the development of the system could be analyzed and established; in objective two the model of the database was elaborated with the pertinent tables for the correct storage of the information; Subsequently, the Extreme Programming agile development methodology was used, which is structured in the phases: planning, design, development and testing, are fundamental for the development of the system due to its scalability. Here we used the ASP.NET programming language using the MVC model (Model, Vista, Controller), using the Microsoft Visual Studio 2012 program, which allowed us to successfully conclude with the third objective. Finally, in order to comply with objective four, verification tests were carried out on the correct functioning of the system where the black box testing tool was used, evaluating the software in its entirety, verifying that all the established requirements were fulfilled, which made it easier to handle and access to technical-scientific information.